Central Corneal Thickness in Ocular Hypertension Patients in Sanglah General Hospital Bali - I Gusti Ayu Ratna Suryaningrum; I Made Agus Kusumadjaja; Ni Made Laksmi Utari (poltekkes kemenkes mataram, 2021)
Ocular hypertension (OH) is a risk factor in glaucoma and modifiable in its early stages. Goldmann applanation tonometer (GAT) is still the gold standard in measuring intraocular pressure (IOP) which is an important parameter in diagnosing and managing glaucoma. Several factors can affect the accuracy of the GAT, one of them is the thickness of the central cornea. This descriptive study was intended to describe the central corneal thickness (CCT) characteristics of the OH patients. The study was conducted at Eye Clinic - Sanglah General Hospital Denpasar which involved 32 patients with 46 eyes diagnosed with HO in 2018. The mean age of subjects was 43.98 (± 17.92), men had a larger proportion (68.1 %). Sixty-six per cent of patients were diagnosed with bilateral OH. In this study, the mean central corneal thickness in HO subjects was 573.81 ± 33.46 μm. The patients' median vertical cup to disc ratio at the time of diagnosis was 0.33, with a mean visual acuity of 0.85. The median value of IOP at the first time of examination was 24.47 mmHg.Central corneal thickness is known to have a positive correlation with IOP, thus affecting the accuracy of IOP measurements. The thicker central corneal thickness will lead to overestimation of the IOP and the thinner one will cause underestimation.